The missing mass. (December 2021) - Atkins, Chris
Abstract : In response to the Lateral Thoughts quiz "Sporting chance", in which question 8 asked for a rough estimate of the theoretical maximum height a pole vaulter could jump, and why the actual world record is slightly above this.